PENGARUH EFEKTIVITAS PEMBELAJARAN KEWIRAUSAHAAN TERHADAP JIWA ENTREPRENEUR SISWA DI MA AL-IHSAN KALIJARING TEMBELANG JOMBANG - Wulandari, Ica Nini; Ashlihah, Ashlihah (Izdihar: Jurnal Ekonomi Syariah, 2023)
This study aims to determine whether there is an influence between Entrepreneurship Learning on the Entrepreneurial Spirit of MA Al-Ihsan Kalijaring Kalikejambon Tembelang Jombang Students. Researchers use survey research, and researchers choose a quantitative approach. Researchers use simple linear regression to calculate the effect of effectiveness in their research. From the results of research at Madrasah Aliyah Al-Ihsan Kalijaring Kalikejambon Tembelang Jombang, it has attempted to increase entrepreneurship learning among students through entrepreneurial subjects, as evidenced by the many supporting subjects that have been given to facilitate students to train their skills, so that the entrepreneurial spirit increases and after After graduating, they are able to become entrepreneurs who create their own jobs, not just looking for work. Keywords : : Entrepreneurship, Entrepreneurial Spirit